Geographic and demographic variation in worry about extreme heat and COVID-19 risk in summer 2020. (March 2023) - Howe, Peter D.; Wilhelmi, Olga V.; Hayden, Mary H.; O'Lenick, Cassandra
Abstract: Extreme heat is a major health hazard that is exacerbated by ongoing human-caused climate change. However, how populations perceive the risks of heat in the context of other hazards like COVID-19, and how perceptions vary geographically, are not well understood. Here we present spatially explicit estimates of worry among the U.S. public about the risks of heat and COVID-19 during the summer of 2020, using nationally representative survey data and a multilevel regression and poststratification (MRP) model. Worry about extreme heat and COVID-19 varies both across states and across demographic groups, in ways that reflect disparities in the impact of each risk. Black or African American and Hispanic or Latino populations, who face greater health impacts from both COVID-19 and extreme heat due to institutional and societal inequalities, also tend to be much more worried about both risks than white, non-Hispanic populations. Worry about heat and COVID-19 were correlated at the individual and population level, and patterns tended to be related to underlying external factors associated with the risk environment. In the face of a changing climate there is an urgent need to address disparities in heat risk and develop responses that ensure the most at-risk populations are protected. Highlights: Survey data-based model of worry about heat and COVID-19 risk across US states. Worry varies by state and across demographic groups. Worry is higher among groups disproportionately impacted by each risk. State-level estimates were related to external risk factors and population composition.